STUDY, DESIGN AND PRODUCTION OF AN AUTOMATIC COTTONSEED WEIGHER IN A BAGGING STATION - SEMASSOU, GUY CLARENCE; AHOUANSOU, ROGER H. (My University, 2021)
This article talks about the design and construction of an automatic weighing system for cotton seeds in a bagging station. It is essentially focused on the weighing of seeds by an automatic weighing system, in order to avoid quantification errors linked to production and the uncertainties of readings linked to traditional weighing. To do this, a system was designed and built with two seed reception hoppers and a feed chute. The system also includes mass sensors, presence detectors and jacks. A PLC is provided and intended for the operation of the process control. It will send information to the pre-actuators from input data (sensors), instructions and a computer program.
Keywords: Automatic Weighing System; Traditional Weighing; Mass Sensors; Presence Detector; Programmable Logic Controller.